A simple game generator for creating audio/tactile games. - Puret A; Archambault D; Monmarché N; Slimane M (Technology & Disability, 2006)
We present in this paper a new game generator that aims at facilitating educators to provide new games scenarios to young visually disabled children. A game scenario description is stored in a XML file without any necessary knowledge of this format from the educator. Moreover, scenarios could be easily shared via a web server.